Brief Report: Adherence Biomarker Measurements in Older and Younger HIV-Infected Adults Receiving Tenofovir-Based Therapy. (1st March 2018) - Seifert, Sharon M.; Castillo-Mancilla, Jose R.; Erlandson, Kristine; Morrow, Mary; Gandhi, Monica; Kuncze, Karen; Horng, Howard; Zheng, Jia-Hua; Bushman, Lane R.; Kiser, Jennifer J.; MaWhinney, Samantha; Anderson, Peter L.
Abstract : Background: Concentrations of tenofovir (TFV) in hair and tenofovir diphosphate (TFV-DP) in dried blood spots (DBSs) as measures of cumulative exposure have been primarily studied in younger, HIV-uninfected individuals taking preexposure HIV prophylaxis. Data on these measures among older HIV-infected individuals are limited. Methods: We evaluated longitudinal TFV and TFV-DP concentrations in hair and DBS, respectively, from HIV-infected adults. Multivariable model variables included age group (18–35 and 60 years and older), creatinine clearance (CrCl), hematocrit (TFV-DP), and gray hair color (TFV). Results: Baseline hair TFV and DBS TFV-DP were moderately correlated [r = 0.5 (0.2 to 0.7); P = 0.001] across both age groups [younger (N = 23) and older (N = 22)]. In adjusted models, CrCl was associated with increases of 15.9% (7.4% to 25.0%); P = 0.0006, and 5.7% (−0.2% to 11.9%); P = 0.057 for TFV in hair and TFV-DP in DBS, respectively, for every 20-mL/min CrCl decrease. Although older age (versus younger age) was univariately associated with increased TFV hair levels, older age was not significantly associated with higher concentrations in hair [−1.4% (−26.7% to 32.7%); P = 0.93] or DBS [4.0% ( − 14.1% to 25.9%); P = 0.68] after adjustment. Similarly, gray color was not significantly associated with higher TFV levels in hair [27.6% (−11.1% to 83.0%; P = 0.18)] in adjusted models. In both adjusted and unadjusted models of TFV-DP levels in DBS, a 1% hematocrit increase was associated with a 3.3% (0.2% to 6.5%) TFV-DP increase ( P = 0.04). Conclusions: Cumulative drug exposure measures (hair and DBS) were comparable in younger and older HIV-infected individuals on TFV-based therapy after adjustment for renal function.